Матеріальна відповідальність працівника: поняття та особливості - Гайдаренко, Л. О.; Haidarenko, L. O. (Право і суспільство. - 2020. - № 2, ч. 2. - С. 33-38, 2020)
Проведено аналіз такої категорії у трудовому праві, як матеріальна відповідальність працівника. Зазначено, що матеріальна відповідальність працівника є різновидом юридичної відповідальності. Відзначено, що матеріальна відповідальність працівника за майнову шкоду, завдану роботодавцеві у зв’язку з невиконанням чи неналежним виконанням ним своїх обов’язків за трудовими правовідносинами, є особливим правовим інститутом трудового права й має тільки їй властиві риси, такі як свій суб’єкт, підстава й умови її настання, види та межі відповідальності, порядок покриття шкоди, цілі та завдання.

The article analyzes the category of labor law as a liability of the employee. It is noted that the employee’s liability is a form of legal liability. This is why legal liability issues need to be considered in detail to answer what a contractual liability of an employee is. It is stated that legal responsibility is an integral part of the legal system in which it performs important functions – it is the legal mechanism that localizes, blocks unlawful behavior and stimulates socially beneficial actions of a person in the legal sphere. Legal responsibility is considered to be broad (philosophical) and in a special legal sense. In the first case, the value of responsibility is explained as the attitude of a person to society and the state, to other people in terms of fulfilling certain requirements, understanding and proper understanding of the citizen’s duties in relation to society, the state and other persons. In a narrow sense, legal responsibility is interpreted as the reaction of the state to the offense committed. In this sense, legal responsibility is the duty of a person to bear certain negative consequences of a stategovernmental nature, provided by law, for the offense. It is emphasized that, depending on various aspects, legal liability can be divided into types, that is, classified on different grounds. The most common in the scientific and educational literature is the classification of legal responsibility for sectoral affiliation. Yes, there is criminal, constitutional, administrative, civil, disciplinary, pecuniary responsibility. It is noted that the liability of an employee for property damage caused to the employer in connection with the non-performance or improper performance of his duties under the employment relationship, is a special legal institution of labor law and has only his own features: his subject, basis and the conditions of its occurrence, types and limits of liability, the procedure for covering the damage, their goals and objectives.

Проведен анализ такой категории в трудовом праве как материальная ответственность работника. Указано, что материальная ответственность работника является разновидностью юридической ответственности. Отмечено, что материальная ответственность работника за имущественный ущерб, причиненный работодателю в связи с неисполнением или ненадлежащим исполнением им своих обязанностей по трудовым правоотношениям, является особым правовым институтом трудового права и имеет только ему свойственные черты, такие как свой субъект, основание и условия его наступления, виды и пределы ответственности, порядок возмещения вреда, цели и задачи.
Employee liability: concepts and features
Гайдаренко, Л. О. Матеріальна відповідальність працівника: поняття та особливості / Гайдаренко Л. О. // Право і суспільство. - 2020. - № 2, ч. 2. - С. 33-38. - DOI: https://doi.org/10.32842/2078-3736/2020.2-2.5.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; трудові правовідносини; labor legal relations; трудовые правоотношения; юридична відповідальність; legal responsibility; юридическая ответственность; матеріальна відповідальність; material responsibility; материальная ответственность; роботодавець; employer; работодатель; працівник; employee; работник